Peran Kepala Sekolah dalam Meningkatkan Minat Membaca Al-Qur’an Siswa SD Negeri Tanambuah - Nisa, Inda Khairun (Borneo Journal of Islamic Education, 2023)
Abstract The role of the school principal in education is needed to increase students' interest in reading the Koran. The principal is the highest leader in the school so that the principal is the key to the success of the school with his ability to inspire enthusiasm throughout the school community. So it can be concluded that the increase in students' interest in reading the Koran is due to the role of the school principal. School principals are not only leaders, but also educators, supervisors, motivators and facilitators. The purpos of this research is to determine the role of the school principal in increasing interest in reading the Al-Qur'an at Tanambuah Elementary School students. As for data collection, the author used observation, interview and documentation techniques. Meanwhile, in analyzing the data, the author uses qualitative methods with data analysis techniques according to Miles and Huberman, namely data collection, data reduction, and drawing conclusions (verification). From the results of this research, it can be seen that the school principal has an important role in increasing students' interest in reading the Koran. School principals must have the right strategy to work together and encourage the participation of all teaching staff to increase students' interest in reading the Koran. The school principal must always motivate and support all school members in order to increase students' interest in reading the Koran. The factor that plays a role in increasing students' interest in reading the Al-Quran at SDN Tanambuah is that teachers can create a good learning environment and give awards to students who excel. Meanwhile, the factor that hinders increasing students' interest in reading the Koran at SDN Tanambuah is inadequate facilities. Keywords: Headmaster, Reading Al-Quran, Student Abstrak Peran dari seorang kepala sekolah dalam pendidikan dibutuhkan untuk meningkatkan minat membaca Al-Qur’an siswa. Kepala sekolah merupakan seorang pemimpin tertinggi di sekolah sehingga kepala sekolah merupakan kunci keberhasilan sekolah dengan kemampuannya menimbulkan semangat seluruh warga sekolah. Sehingga dapat disimpulkan bahwa meningkatnya minat membaca Al-Qur’an siswa disebabkan adanya peran dari kepala sekolah. Kepala sekolah yang tidak hanya sebagai pemimpin, tapi juga sebagai pendidik, supervisor, motivator dan fasilitator.Tujuan penelitian ini untuk mengetahui peran kepala sekolah dalam meningkatkan minat membaca Al-Qur’an siswa SDN Tanambuah. Adapun pengumpulanedata, penulis menggunakan teknik observasi, wawancara dan dokumentasi. Sedangkan dalam menganalisis data, penulis menggunakan metode kualitatif dengan teknik dalam menganalisis data menurut miles dan huberman yaitu pengumpulan data, reduksi data, dan penarikan kesimpulan (verifikasi). Dari hasil penelitian tersebut terlihat bahwa kepala sekolah mempunyai peranan penting dalam meningkatkan minat membaca Al-Quran siswa. Kepala sekolah harus mempunyai strategi yang tepat untuk bekerja sama dan mendorong peran serta seluruh tenaga pengajar untuk meningkatkan minat membaca Al-Quran siswa. Kepala sekolah harus selalu memotivasi dan mendukung seluruh warga sekolah agar dapat meningkatkan minat membaca Alquran murid. Faktor yang berperan dalam meningkatkan minat membaca Al-Quran siswa di SDN Tanambuah adalah guru dapat menciptakan lingkungan belajar yang baik dan memberikan penghargaan kepada siswa yang berprestasi. Sedangkan faktor yang menghambat peningkatan minat membaca Alquran siswa di SDN Tanambuah adalah fasilitas yang kurang memadai. Kata Kunci: Kepala Sekolah, Membaca Al-Qur’an, Siswa